Kepastian Hukum Atas Kebocoran Data Pribadi Pengguna Aplikasi Online - Mevanisa Berlian Mochtar (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2023)
Technology is essential for human progress. Nowadays, everyone is involved in technology. our personal identity is also stored in the electronic state database system. Various new online applications are created to support human life, making human work easier and faster. to use these online applications, we must register our personal data. However, the more sophisticated the technology, the more ways for criminals to carry out their actions. many hackers carry out their actions to steal other people's personal data, not even hesitating to attack government agencies. With the urgency of personal data theft, Indonesia passed a law governing personal data protection. the new rules are still very new and must be applied properly.